2004
DOI: 10.1097/00000542-200407000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Primary Anesthetic Regimen Can Influence Intensive Care Unit Length of Stay after Coronary Surgery with Cardiopulmonary Bypass

Abstract: The use of sevoflurane and desflurane resulted in a shorter ICU and hospital LOS. This seemed to be related to a better preservation of early postoperative myocardial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
87
2
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(93 citation statements)
references
References 0 publications
1
87
2
3
Order By: Relevance
“…As there was no previous study on the left ventricular stroke work in off-pump CABG under desflurane and propofol anaesthesia, sample size calculation was based on results of the study on the difference in dp/dt change between desflurane and propofol after CABG surgery with the use of CPB [5]. Presuming standard deviation of the difference as 15% and difference in the change of LVSWI 12% between groups, a two-sample t-test would require a sample size of 25 patients per group to achieve 80% power with α = 0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there was no previous study on the left ventricular stroke work in off-pump CABG under desflurane and propofol anaesthesia, sample size calculation was based on results of the study on the difference in dp/dt change between desflurane and propofol after CABG surgery with the use of CPB [5]. Presuming standard deviation of the difference as 15% and difference in the change of LVSWI 12% between groups, a two-sample t-test would require a sample size of 25 patients per group to achieve 80% power with α = 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Both propofol and volatile anaesthetics, in addition to opioids and muscle relaxants, are widely considered safe during coronary surgery, being free from significant haemodynamic compromise. Volatile anaesthetics have been reported to exert cardioprotective effects referred to as 'anaesthetic conditioning' , exceeding propofol-related myocardial protection [1][2][3][4][5]. Similarly to sevoflurane and isoflurane, desflurane has also been demonstrated to reduce the serum concentration of myocardial necrosis biomarkers and improve heart function in patients undergoing cardiopulmonary bypass coronary surgery [1].…”
mentioning
confidence: 99%
“…Many studies (11)(12)(13)(14)(15)(16)18,19) and reviews (21)(22) have appeared in the literature suggesting a cardioprotective effect provided by volatile anesthetics in patients undergoing cardiac procedures. A recent survey (23) conducted in 64 Italian centres, encompassing a total of 34,310 patients undergoing coronary artery bypass graft surgery, showed that risk-adjusted mortality may be reduced by the use of volatile agents.…”
Section: Discussionmentioning
confidence: 99%
“…All but one of the 22 randomized controlled studies included in the meta-analysis studied low risk patients undergoing isolated procedures (mostly coronary artery bypass grafting). Studies performed on patients undergoing coronary artery bypass graft (CABG) surgery, either with cardiopulmonary bypass (CPB) (11)(12)(13) (19) showed that an anesthetic plan with sevoflurane was associated with better preservation of cardiac function and lower cardiac troponin release peak in patients undergoing aortic valve replacement for aortic stenosis. Large multicentre randomized controlled studies in high risk populations of patients are needed to evaluate the possible influence of different anesthetic regimens on patient outcomes after cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The potentially beneficial effects of APC in patients have also been reported. (4,5,(13)(14)(15)(16)(17) Initially, the mechanisms by which volatile anesthetics exert protective actions on ischemic myocardium have previously been attributed to an improvement in the relation between myocardial oxygen supply and demand. For instance, our research has reported that volatile anesthetics are negative inotropes that decrease left ventricular contractility and depress sino-atrial nodal function.…”
mentioning
confidence: 99%